Hitting rewind with you. 1 - Kira, Hanamaru (Kodansha America, Inc, 2026)
Wakaba Kayano is a 20-year-old college student who was too busy studying in high school to experience the quintessential personal milestones of her teenage years, like going on an afterschool date. In a moment of desperation, she goes out on Halloween in her old high school uniform in an effort to take back some of those heart-fluttering experiences she never had, and in doing encounters Fumito, a boy clad in the quintessential high school boy uniform. Whisked away on the date of her dreams, she panics when forced to reveal her true age-only to find out that Fumito is in college, too!